Assessing Awareness Level about Warning Signs of Cancer and its Determinants in an Iranian General Population - Feizi, Awat; Kazemnejad, Anoshirvan; Hosseini, Mohsen; Parsa-yekta, Zohreh; Jamali, Jamshid (Journal of Health, Population and Nutrition, 2012)
The present study was aimed at investigating the awareness level about warning signs of cancer and its determinants in an Iranian general population. This cross-sectional interview-based survey investigated 2,500 people aged 18 years and over, as a representative sample of Tehran population. Latent class regression was applied for analyzing data. A small (18.8%) proportion of the respondents had high level of knowledge, and 54.5% had moderate awareness, and 26.7% had low level of awareness. Most effective predictors for awareness were educational attainment, sex, and marital status. The findings suggest that the overall level of knowledge about warning signs of cancer among the public is low, particularly about some specific signs. Accordingly, educational and intervention programmes, with special attention placed on particular at-risk populations, to increase awareness about the disease leading to its early diagnosis are needed. DOI: http://dx.doi.org/10.3329/jhpn.v29i6.9904 JHPN 2011; 29(6): 656-659